The New Paradigm of Physical Education: SLR Analysis of AI in Handball Measurement Tests and SDGs-Based Eco-Friendly Facilities - Dyas Andry Prasetyo; Mohammad Hasan Basri (CV. Bimbingan Belajar Assyfa, 2026)
Purpose: This study aims to systematically analyze the role of artificial intelligence (AI) in optimizing handball measurement test instruments while integrating environmentally friendly facility management to support Sustainable Development Goals (SDGs) within physical education. Methodology: Employing a Systematic Literature Review (SLR) based on PRISMA design, this research analyzed literature from Scopus and ERIC databases using VOSviewer and Harzing’s Publish or Perish software. Findings: The results demonstrate that AI integration significantly enhances the objectivity of motor assessment and improves the efficiency of facility management, with teacher digital literacy identified as a critical scaffolding variable for successful implementation. Furthermore, the findings reveal that facilities lacking sustainability principles fail to provide long-term contributions to students’ psychomotor development in a global context. Implications: This new paradigm necessitates a repositioning of the physical education curriculum that synergizes smart technology with green facility management. Recommendations: Institutions are encouraged to adopt AI-driven evaluation tools and prioritize sustainable infrastructure design to create an inclusive, efficient, and ecologically responsible future for sports education. Originality/Value: By bridging the gap between digital transformation and environmental sustainability in physical education, this research provides a comprehensive framework for addressing the limitations of manual assessment methods and infrastructure management, offering a strategic approach to modernizing the field in line with global sustainability targets.